ECONOMIC STRUCTURE AND POVERTY IN MEXICO, 2008-2018 - Padilla Moran, Carlos; Bracamontes Nevárez, Joaquín (KAIRÓS, revista de ciencias económicas, jurídicas y administrativas, 2022)
This study analyzes the economic structure and whether the changes it experiences are linked to and affect poverty in Mexico and the states that comprise it. Therefore, the GDP and employment sectoral participation, the intersectoral effect (EI), and the reassignment effect (ER) of employment towards high productivity sectors in the States that make up the country are estimated, and Coneval poverty indices are also used in the analysis. The evidence confirms that the sectoral participation with respect to GDP and employment tends to increase in the services sector and that in the country, the increase in productivity is mainly attributed to RE; however, the activities to which employment is relocated in the states are primarily non-industrial activities. Finally, it was found that the poverty reduction is explained by economic growth, the participation of the secondary and tertiary sectors of the economy, but not by the reallocation effect, which denotes the non-existence of a structural change in the Mexican economy.